Optimization of the Plastic Area of a Borehole Based on the Gas Extraction Effect and Its Engineering Application - Kuan Wu; Shiliang Shi; Yi Lu; He Li; Min Li (Geofluids)
Gas extraction is most commonly used to control gas disasters in coal mines. The distribution of the plastic zone around a borehole and the sealing quality are key factors affecting gas extraction. In this paper, the plastic zone was simulated by COMSOL, and a theoretical equation of the plastic zone radius was derived. In addition, an antispray hole equipment and the “two plugging and one injection” sealing technology were proposed. The results show that a larger borehole pore size corresponds to a larger plastic zone and larger range of pressure relief of the borehole. The error between the calculated and simulated plastic zone radii is within 1%, and the modified equation is applicable to Puxi mine. The loss and harm caused by borehole spraying are reduced by applying antispray hole equipment. By applying the “two plugging and one injection” sealing technology and phosphogypsum-based self-produced gas expansion paste material to block the borehole, the sealing quality is improved and an accurate gas mixing flow, pure flow, and concentration were obtained. As the plastic zone enlarges, the gas extraction flow gradually increases with, but the relative variation of flow first increases and subsequently decreases. Considering the safety and economy of construction, the optimal radius of the plastic zone is 64.9 mm.